AN INSIGHT TO MODERN ANALYTICAL TECHNIQUES FOR DENDRIMER CHARACTERIZATION (CAHIERS MAGELLANES-NS, 2024)
The solubility and permeability of the drug have a significant impact on the bioavailability of a number of drug administration routes. Pharmaceutical formulation faces a significant difficulty in optimizing these crucial variables without making structural modifications. As a result, research has shown that dendrimers are new and offer a viable method for delivering targeted drugs. The physiochemical characteristics of dendrimers are defined by a wide range of characterization techniques and a number of preparation methods for a variety of dendrimers, each with specific benefits. It is challenging to discern between the morphological and structural characteristics of the synthesized dendrimers since there is a dearth of strong theoretical knowledge on dendrimer characterization. This study outlines an insightful literature assessment that ensures the choice of an appropriate analytical approach to support the structural characterization of dendrimers.